A New Species of Curvularia Boedijn - Bharadwaj, S. D. (Indian Forester, 1969)
A new species of Curvularia Boedijn, C. desmodii sp. nov. is described. The fungus infects the leaves of Desmodium gangeticum DC. and Uraria picta Desv. causing serious leaf spot disease in the Banaras Hindu University (B.H.U.) campus. The fungus is compared with the species of Curvularia1-4 incorporated in the lunata group, specially with C. trifolii from which it differs in measurements and colour of conidia, branched conidiophores, presence of prominent hilum at the base of conidia and formation of chlamydospores in hyphae.